Mobile-Based Technology for Data Management of Students Fieldwork Practices - Nandang Hermanto; Alya Khansa Dzakkiyah (LPPM Universitas Islam 45 Bekasi, 2021)
Fieldwork Practices (PKL) is one of the activities in the vocational teaching and learning process which takes place in a direct business environment. The main purpose of implementing PKL is to introduce students to the real work. The implementation of PKL at SMK Ma'arif NU 1 Sumpiuh is carried out for 6 months which is divided into 2 implementation activities, namely 3 months in odd semester and 3 months in even semester. The purpose of this study is to provide a suggestion to facilitate the process of recording PKL student data both in odd and even periods. In addition, the proposed system also provides details on the location of PKL and provides if in the second stage of PKL implementation there are students who change the location. The PKL application has gone through the system functional testing phase and has been running according to the needs of the PKL activity process. The technology used in this study uses a mobile so that all activities both from the school, committee and students can be monitored in real time by all related parties.